Intergenerational Dialogue in Humanities Education: Integrating Age Perspectives in Undergraduate Pedagogy - Liu, Roya (Age, Culture, Humanities: An Interdisciplinary Journal, 2025)
This pedagogical essay addresses college students’ lack of engagement with aging—a challenge rooted in institutional unpreparedness to embrace age perspectives that has become increasingly urgent amid growing calls for intergenerational solidarity. Using a 100-level English course, “Intergenerational Dialogue: Modernism and Contemporary Literature,” as a case study, I propose a new pedagogy of “intergenerational dialogue” for integrating age perspectives into general-education humanities courses. The course stages figurative dialogues between twentieth and twenty-first-century texts. Unlike traditional approaches that focus on intergenerational relations among real people or those depicted in texts, this method explores how a dialogic relationship between texts from different generations can inform real-world intergenerational exchange. The essay first argues for the significance of this pedagogy beyond age studies by suggesting the rich potential of an intergenerational lens for rethinking literary history. It then demonstrates how this pedagogy was put into classroom practice through: pre-class questions that directed students’ critical attention to age-related depictions, intergenerational comparisons of paired texts, and assignments that practiced the method. I also explain how this approach, while borrowing from comparative practices common in classroom settings, advances scholarly efforts to move beyond the traditional mode of “compare and contrast” toward a fluid, relational model. The paper concludes with reflections on areas for improvement for future critical inquiry into this pedagogy.